PKM Leksem “ALLAH” Tanpa Bergaya Bahasa Personifikasi Kepada Jemaah Solat Mesjid Al Hikmah Kecamatan Medan Tembung - Ahmad Laut Hasiibuan; Rosmawati Harahap; Rahmat Kartolo; Effendi Barus (LPPI UMN AL WASHLIYAH, 2024)
Socialization activities related to the urgency of how to speak well in conveying Islamic material well without hurting feelings or offending other religions is something very basic. The aims of PKM are (1) to increase understanding of how to speak in Islamic da'wah communication, (2) to improve understanding of the concept of Allah as Rabb for participants. The method used in socializing the lexeme